Investigating Factors Affecting Capital Structure of Equitized State-Owned Enterprises in Ho Chi Minh City - Tran, Thi Thuy Linh (University of Economics Ho Chi Minh City, 2023)
Using panel data along with the application of Pooled OLS, FEM, and REM estimates, this study conducts an investigation into the effects of a series of factors, namely state ownership, size, tangible assets, growth, return on assets (ROA), effective tax rate, and liquidity, on capital structure of 165 HCMC-based equitized state-owned enterprises (SOEs), categorized into three groups over the 2008–2012 period. As suggested by the findings, tangible assets, ROA, and liquidity are negatively related to leverage ratio and short-term debt ratio for the three groups of enterprises. In terms of firm size, there exists a positive correlation with leverage ratio and short-term debt ratio for Group 1 and 2 but a negative correlation with short-term debt ratio for the case of Group 3.